Investigation of cardiotoxicity by dipeptidyl-peptidase-4 inhibitors in a human cardiomyocyte cell line as well as in samples from chronic heart failure patients. (10th June 2022) - Voros, I; Onodi, ZS; Toth, VE; Gergely, T; Saghy, E; Gorbe, A; Kemeny, A; Leszek, P; Helyes, ZS; Ferdinandy, P; Varga, ZV
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020 research and innovation programme, Ministry for Innovation and Technology Background: Dipeptidyl-peptidase-4 (DPP4) inhibitors are relatively new therapeutic tools for type 2 diabetes. The SAVOR-TIMI-53 clinical trial has revealed an increased heart failure (HF)-associated hospitalization rate in saxagliptin treated patients. Although this critical side effect could limit the therapeutic use considerably, the mechanism by which DPP4 inhibitors damage the heart is still unclear. Aims: We aimed to set up a relevant cellular platform to investigate mechanistically DPP4 inhibition, and the role of its potentially important neuropeptide substrates (e.g. Substance P and Neuropeptide Y). Moreover, we aim to determine the expression of DDP4 and its neuropeptide substrates in human and cellular samples. Methods: Western blot, ELISA, and radioimmunoassay experiments were performed to investigate the expression of DPP4 and its neuropeptide substrates in human hearts and in AC16 cells. Viability measurements with calcein staining and scratch assay experiments were used to test the potentially toxic effect of DPP4 inhibitors. The localization of DPP4 mRNA was determined with RNA Scope in situ hybridization. Results: Expression of DPP4 and NPY proteins decreased in interventricular septum samples of patients with HF compared to healthy controls. In human hearts DPP4 mRNA is detectable in cardiomyocytes, while other cell types (endothelial cells, fibroblasts, and macrophages) show negligible expression. AC16 human cardiomyocyte cell line expresses DPP4 enzyme.  Treatment with various DPP4 inhibitors administered alone or in combination with neuropeptides don't affect cellular survival; although, in scratch assay experiments treatments with neuropeptides decreased cell migration speed in the isolated neonatal rat cardiomyocyte-fibroblast co-culture. The migration speed reducing effect of NPY was revered by the administration of saxagliptin at the highest concentration of NPY. Conclusions: Decreased activity of DPP4 may play a role in the pathomechanism of end-stage congestive heart failure. The DPP4 enzyme could be important as a compensating mechanism against the elevated sympathetic activity in HF and for the altered neuropeptide tone. Inhibition of DPP4 could decrease this adaptive mechanism thereby exacerbating myocardial damage.